Improved Crystalline Quality of AlN by Epitaxial Lateral Overgrowth Using Two-Phase Growth Method for Deep-Ultraviolet Stimulated Emission - Xiang Chen; Jianchang Yan; Yun Zhang; Yingdong Tian; Yanan Guo; Shuo Zhang; Tongbo Wei; Junxi Wang; Jinmin Li (IEEE Photonics Journal)
We report on the maskless epitaxial lateral overgrowth (ELOG) of the AlN layer on trench-patterned AlN/sapphire templates by metal-organic chemical vapor deposition (MOCVD). With a two-phase growth of different V/III ratio at a relatively low growth temperature of 1250 °C, up to a 7.3-μm-thick high-quality crack-free AlN film with a threading dislocation density of 8 × 108 cm–2 was obtained. Compared with the 0.9-μm AlN film grown on a planar sapphire substrate, the ELOG-AlN film has a lower dislocation density and a much better strain state, regardless of its 7.3-μm thickness. Compared with the single low V/III ratio growth, the two-phase growth method can lead to a coherent coalescence at the second growth stage and hence suppress new dislocations generating at the coalescence fronts. Stimulated emission was observed from Al(Ga)N multi-quantum-wells laser grown on the ELOG-AlN template with low dislocation density. The deep-ultraviolet laser (DUV) on these templates exhibited lasing at 263.3 nm with the spectral linewidth of 1.29 nm and threshold pumping power density of 2.7 MW/cm2 at room temperature.